2021
DOI: 10.1017/s0007114521001422
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of dairy products and CVD risk: results from the French prospective cohort NutriNet-Santé

Abstract: In France, dairy products contribute to dietary saturated fat intake, of which reduced consumption is often recommended for cardiovascular disease (CVD) prevention. Epidemiological evidence on the association between dairy consumption and CVD risk remains unclear, suggesting either null or inverse associations. This study aimed to investigate the associations between dairy consumption (overall and specific foods) and CVD risk in a large cohort of French adults. This prospective analysis included participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It may also be difficult to disentangle the potential physiological roles of FA from those of the rest of the dairy food matrix, which is highly variable among dairy food groups such as cheese and butter (97,98) . In addition, it has been proposed that fermented dairy foods such as yogurts may help prevent obesity via beneficial effects on the gut microbiota, the intestinal barrier function and the hormonal regulation of appetite (99) and may be associated with lower risks of cerebrovascular diseases (100) .…”
Section: Discussionmentioning
confidence: 99%
“…It may also be difficult to disentangle the potential physiological roles of FA from those of the rest of the dairy food matrix, which is highly variable among dairy food groups such as cheese and butter (97,98) . In addition, it has been proposed that fermented dairy foods such as yogurts may help prevent obesity via beneficial effects on the gut microbiota, the intestinal barrier function and the hormonal regulation of appetite (99) and may be associated with lower risks of cerebrovascular diseases (100) .…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the full text of the remaining reports, leading to the exclusion of another 177. In the end, we included 64 publications [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] ] that prospectively analyzed 45 unique cohorts. There were 19 publications [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies assessed dietary intake using food frequency questionnaires. The remaining studies used a modified diet history method in the case of the Swedish Malmö Diet and Cancer cohort [ 43 , 46 , 87 , 89 ], dietary history interview in the case of the Finnish Mobile Clinic Health Examination Survey [ 61 ], 3-day weighted dietary records in the case of the NIPPON DATA80 study [ 85 ], 24-hour dietary records in the case of the NutriNet-Santé study [ 93 ], or a dietary questionnaire combined with a 7-day record in the case of the United Kingdom and Malmö cohorts [ 53 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to cardiovascular diseases, since milk and milk products can be a source of saturated fatty acids, their regular consumption could be linked to increased risks of these diseases. However, it has been shown that the consumption of dairy products with a low-fat content does not mean additional risks of cardiovascular diseases (Drouin-Chartier et al 2016;Fontecha et al 2019;Sellem et al 2022).…”
Section: Introductionmentioning
confidence: 99%